A Fragment of an Ancient Hymnody Manuscript from Mǝʾǝsar Gwǝḥila (Tǝgray, Ethiopia) - Nosnitsin, Denis; Rabin, Ira (Aethiopica, 2014)
The article presents a multidisciplinary analysis of an old fragment of a hymnody manuscript recently recorded in one of the ecclesiastic libraries of East Tǝgray. The handwriting on the fragment demonstrates pre-14th century palaeographic features. A peculiarity of the text is represented by the so-called “odd vocalization”, with many words vocalized in a way different from the standard Gǝʿǝz. The content of the fragment is a sequence of antiphons, some having been identified. A non-destructive material analysis, aimed at identifying the chemical components of the inks, revealed that the black ink used in the fragment is dissimilar from the common carbon inks attested in more recent manuscripts of the same ecclesiastic library. It does contain a high quantity of iron and a few other metals; however, it cannot be plainly identified as iron-gall-inks.